Perancangan Sistem Manajemen Restoran dengan Aplikasi Pemesanan Restoran Berbasis Mobile dalam Jaringan Lokal - Manggala Raka Perkasa; Rinta Kridalukmana; Eko Didik Widianto (Department of Computer Engineering, Engineering Faculty, Universitas Diponegoro, 2016)
In modern times, like today, the role of software or applications that run on top of the platform is very important. This is because almost all of the work done by the people, made by the software or application. Applications can be used to assist in the processing of data and upload the final report. Data recorded previously processed by the paper can be recorded and processed by the application so that more efficiently.Development of an information systemin this study using the method of waterfall. Waterfall model consist of: requirements, design, implementation, testing and maintenance. For the start of the design, developer need to observations or interviews to determine the needs of the system that being developed. Application developed using the framework Codeigniter. System Management Restaurant build for help uses that has restaurant to manage activity in there like order menu, processing menu in kitchen, make invoice for custumer, and generate report of finance. This application can be expected to help user in process data efficiently so thet improve wuality of restaurant in terms of service and time. This system has a 5 user that consisting of waiters, chef, cashiers, manager, owner which every user has different privilege. System management restaurant developed using web-based programming which support in mode client server and uses MySQL as a database management storage.